Development of an External Radiation Dose Estimation Model for Children Returning to Their Homes in Areas Affected by the Fukushima Nuclear Accident. Issue 6 (December 2019) - Mori, Airi; Takahara, Shogo; Yoshida, Hiroko; Sanada, Yukihisa; Munakata, Masahiro
Abstract : Abstract: On 1 April 2017, around 6 y after the Fukushima Daiichi nuclear power station accident, evacuation orders for large affected areas were lifted, and areas to which people could return were expanded. In the current study, a dose estimation model based on a probabilistic approach has been developed to estimate the external radiation doses children would receive after returning to these areas. The target groups are children from infants to high school students, and the target areas are nine municipalities including evacuation areas as of 5 September 2015. The estimation period is for 4 y starting 1 April 2017. Validation of the model in an area for which individual personal dosimetry measurements were available showed that it is valid for infants, kindergarteners, 3rd and 4th grade elementary school students, 5th and 6th grade elementary school students, and junior high school students. Considering the statement of the International Commission on Radiological Protection, the estimated radiation doses for these five age groups were taken to be the 95th percentiles of the predicted distributions as an index of conservative judgement. As a result of our estimations, the 95th percentile doses to all age groups were less than 20 mSv y −1 in all periods and in all areas. The 95th percentile doses in some areas were less than 1 mSv y −1, which is the long-term dosimetric target set by the Japanese government. It should be noted that our results are preliminary, being based on several assumptions and limitations regarding environmental contamination conditions and the behavioral patterns of children. To estimate the children's doses precisely, further considerations for these assumptions and limitations will be needed.